The Restructured Landscape of Economic Development: Challenges and Opportunities for Regional Workforce Development Collaborations. (May 2015) - Meléndez, Edwin; Borges-Mendez, Ramon; Visser, M. Anne; Rosofsky, Anna
Regional workforce development collaborations have emerged as a notable approach to tackle complex problems within workforce development systems. While much of the existing research on workforce development documents the importance of promoting regional workforce development collaborations, little research exists that adequately identifies the specific barriers that organizations encounter in establishing and maintaining these collaborations. Through several sets of interviews over a 10-year period, this article examines the experiences of three detailed case studies of regions—Greater North Bay area, CA; Greater Fort Wayne/Northeastern IN; and Greater Pittsburgh/Southwestern PA—to identify the barriers and emerging strategies for creating regional workforce development systems. The authors identify three primary barriers: high initial upfront costs, competition, and fragmentation. They also find that an effective regional workforce development system is promoted primarily through an anchor organization that possesses programmatic and jurisdictional authority throughout a region.